Tunable bandpass filter with independently controllable dual passbands - Huang, Xiaoguo (2013)
This paper presents a two-pole dual-band tunable bandpass filter (BPF) with independently controllable dual passbands based on a novel tunable dual-mode resonator. This resonator principally comprises a λ/2 resonator and two varactor diodes. One varactor is placed at the center of the resonator to determine the dominant even-mode resonant frequency; the other is installed between two ends of the resonator to control the dominant odd-mode resonant frequency. These two distinct odd- and even-mode resonances can be independently generated, and they are used to realize the two separated passbands as desired. Detailed discussion is carried on to provide a set of closed-form design equations for determination of all of the elements involved in this tunable filter, inclusive of capacitively loaded quarter-wavelength or λ/2 resonators, external quality factor, and coupling coefficient. Finally, a prototype tunable dual-band filter is fabricated and measured. Measured and simulated results are found in good agreement with each other. The results show that the first passband can be tuned in a frequency range from 0.77 to 1.00 GHz with the 3-dB fractional-bandwidth of 20.3%-24.7%, whereas the second passband varies from 1.57 to 2.00 GHz with the 3-dB absolute-bandwidth of 120 ± 8 MHz.